Role of the tumor microenvironment in malignant melanoma organoids during the development and metastasis of tumors - Zhou, Siyu; Lu, Jinghan; Liu, Shiyang; Shao, Jiaqi; Liu, Zhanwei; Li, Jianjun; Xiao, Wan’an (Frontiers in Cell and Developmental Biology, 2023)
Malignant melanoma (MM) is the most metastatic and aggressive form of skin cancer, and carries a high risk of death. Immune-checkpoint inhibitor therapy and molecular-targeted therapy can prolong the survival of patients with advanced MM significantly. However, the low response rate and inevitable drug resistance prevent further improvements in efficacy, which is closely related to the tumor microenvironment (TME). The TME refers to the tumor stroma, including fibroblasts, keratinocytes, immune cells, soluble molecules, and extracellular matrix (ECM). The dynamic interaction between the TME and tumor cells is very important for the growth, local invasion, and metastatic spread of tumor cells. A patient-derived organoid (PDO) model involves isolation of tumor tissue from patients with MM and culturing it in vitro in a three-dimensional pattern. Compared with traditional cultivation methods, the PDO model preserves the heterogeneity of the tissue structure of MM and demonstrates the interaction between MM cells and the TME. It can reproduce the characteristics of proliferation, migration, and invasion of MM cells, and better simulate the structural function of MM in vivo. This review explores the role of each TME component in development of the PDO model. This review will provide a reference for research on the drug screening and targeted treatment using PDOs, particularly for the immunotherapy of MM.